Estimating the economic cost of carbapenem resistant Enterobacterales healthcare associated infections in Singapore acute-care hospitals. - Yiying Cai; Grace S R Hoo; Winnie Lee; Ban Hock Tan; Joanne Yoong; Yik-Ying Teo; Nicholas Graves; David Lye; Andrea L Kwa (Public Library of Science (PLoS), 2022)
Quantifying the costs of hospital associated infections (HAIs) caused by carbapenem-resistant Enterobacterales (CRE) can aid hospital decision makers in infection prevention and control decisions. We estimate the costs of a CRE HAI by infection type and the annual costs of CRE HAIs to acute-care hospitals in Singapore. We used tree diagrams to estimate the costs (in Singapore dollar) of different CRE HAI types from the health service perspective and compared them to the costs of carbapenem-susceptible HAIs. We used two approaches to estimate costs-direct costs of consumables for infection prevention and treatment; and costs associated with lost bed days. Cost of a HAI were extrapolated to annual CRE HAI incidence in Singapore acute-care hospitals to estimate the annual cost to the hospitals. We found that the cost of a CRE HAI based on direct cost and lost bed days are SGD$9,913 (95% CI, SGD$9,431-10,395) and SGD$10,044 (95% CI, SGD$9,789-10,300) respectively. CRE HAIs are markedly higher than the carbapenem-susceptible HAIs for all infection types. In both approaches, CRE pneumonia was the costliest infection. Based on a CRE HAI incidence of 233 per 100,000 inpatient admissions, CRE HAIs costed SGD$12.16M (95% CI, SGD$11.84-12.48M) annually based on direct costs, and SGD$12.33M (95% CI, SGD$12.01-12.64M) annually based on lost bed days. In conclusion, we described the cost of CRE HAIs in Singapore hospitals and identified infections with the highest costs. The findings may be useful in informing future economic evaluations of competing CRE HAI prevention and treatment programmes.